Development of Teaching Materials for Writing Narrative Texts Based on Local Wisdom for Primary School Students - Valentri, Avi; Rahayu, Maulina; Ariestika, Elsa (Faculty of Education Universitas Negeri Malang, 2024)
The aim of this research is to obtain innovation in teaching materials for writing local wisdom-based narrative texts for elementary school students. The research method used is development (R&D) with the model used is ADDIE. The ADDIE model has five stages, namely analysis, design, development, implementation, and evaluation. The sample used for the trial was SD Negeri 02 Serang City, consisting of 85 students with the sampling technique used, namely purposive sampling. The data collection instrument consists of a validation sheet for material experts, practitioner experts, media experts and a feasibility test questionnaire for elementary school students. The research results show that the development of teaching materials for writing narrative texts based on local wisdom for elementary school students can be used in learning to write narrative texts with very valid criteria and is suitable for use after being tested with research samples. This can be seen from the average of three validator experts, namely language validators with an average percentage of 83.33%, material validators 89.33%, and media validators 88.33%. Based on data collection from the three experts, an average percentage of 86.97% was obtained with a very valid interval and suitable for use.